Strategic and professional leadership : the challenge of role duality - Weight, Pauline (Cranfield University, 2001)
In 1983 the National Health Service in England moved from a functional to a general management philosophy. This fundamental change gained momentum with the introduction of NHS Trusts in the early 1990s. Since this period, clinicians have taken a greater role in the strategic leadership of their organisations. This research considers the role of senior doctors (consultants) who have taken up a strategic leadership role alongside their clinical role (role duality). This is a qualitative study centred on the perceptions of individuals in this role in three NES Trusts. A new understanding of the dual role is developed through a methodology linked to frameworks from existing research. The role is viewed through a role theory perspective and put into context by understanding existing research on the role itself and relevant areas of the career, strategic leadership and management literatures. The uniqueness of this research is to understand how individuals take up the challenge of role duality; there is a need to comprehend how individuals perceive the clinical role and the strategic leadership role in equal measure. This approach drives the methodology and the design of interviews as the main source of data. The findings are many with new insights and confirmation of some existing understanding of how role duality is taken up and the differences and similarities between the two main elements of the dual role. The different approaches to taking up the dual role within and across the trusts are seen as clustering around two dimensions, taking charge and managerial alignment. Consequences of the different approaches range ftom a possibility of failure or being ineffective, to a gradual development of the service and the development and delivery of the organisation's strategy.